Seletividade dos herbicidas Bentazon e Nicosulfuron para Crotalaria juncea e Crotalaria spectabilis em consórcio com a cultura do milho - Nogueira, Cassio Henrique Pereira [UNESP] (2015)
The species Crotalaria juncea and C. spectabilis have benefits suach as nutrients input in soil, straw production for no-tillage system, weed management and the nematicide potential. In doing so, corn intercropped with crotalaria allows better use of the agricultural year, having in the same period, economic return from grain yield and the benefits of the legume species. However, there are few informations about the the selectivity of herbicides, weed management and the interference from the legumes species in the development of corn culture, especially when in simultaneous sowing. With the objective to study the selectivity of the herbicides bentazon and nicosulfuron, isolated and in mixture, to Crotalaria juncea and C. spectabilis, when established in intercrop with corn, the weed control and the corn development in this production system. Two experiments were conducted in pots, kept in environment conditions, for selection of herbicides and dosages used in the field. In the next step, four experiments were set up in the field, two for each species, one during the late-season growing period and another one in regular growing season period. In these, the experimental design was the randomized block, with 14 treatments and four replicates. Eight treatments with herbicides were studied: bentazon (720 e 960 g i.a. ha-1), nicosulfuron (16 e 48 g i.a. ha-1) and bentazon plus nicosulfuron (720 + 16; 720 + 48; 960 + 16; 960 + 48 g i.a. ha-1). Moreover, six controls were maintained: sole corn and sole sunn hemp (with and without weeds) and corn and sunn hemp intercropped (with and without weeds). The herbicide bentazon isolated, in both dosages tested, was selective to C. juncea and C. spectabilis. Nicosulfuron in 48 g i.a. ha-1, isolated or in mixture with bentazon, promoted the best weed control. Corn affected the recoverability of C. juncea and C. spectabilis plants treated with herbicides. C. juncea intercropped without herbicides or ...